2008
DOI: 10.1093/jjco/hyn066
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine in Present Day Oncology Care: Promises and Pitfalls

Abstract: Cancer is already a well-recognized global phenomenon. The traditional approaches to cancer therapy have been surgery, radiotherapy and chemotherapy. These modalities have shown considerable promise and presently form cornerstones of management of most malignancies. However, these conventional approaches have associated toxicities and suffer from limitations in curing advanced lesions. Complementary and alternative medicine (CAM), for reasons varying from cost to accessibility, has assumed significant importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
(56 reference statements)
0
13
0
1
Order By: Relevance
“…Direct comparison between studies is rather difficult since in the literature CM methods are not categorised uniformly and may also involve non‐oral interventions like energy therapies, as well as mind and body manipulations (Munshi et al . ). However, recent study revealed that 45% of breast cancer patients used ‘oral CM products’ during radiotherapy (Moran et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Direct comparison between studies is rather difficult since in the literature CM methods are not categorised uniformly and may also involve non‐oral interventions like energy therapies, as well as mind and body manipulations (Munshi et al . ). However, recent study revealed that 45% of breast cancer patients used ‘oral CM products’ during radiotherapy (Moran et al .…”
Section: Discussionmentioning
confidence: 97%
“…CM methods are mainly used with the hope that they increase the efficacy of anti-cancer therapy (Evans et al 2007). CM may be also utilised to alleviate side effects of conventional therapies, such as increased levels of fatigue, anxiety, depression, and deterioration of quality of life (Munshi et al 2008). Additionally, patients may be more prone to CM due to the limitations of conventional therapy or desire for natural treatments (Simon et al 2007;Olaku & White 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, little is known about the safety, efficacy, mechanisms of action, and cost-effectiveness of most CAM therapies. 4 Use of CAM by patients with cancer has been reported exhaustively, especially among Western or Far Eastern populations.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic painful musculoskeletal conditions are very common and the use of drugs of Complementary & Alternative System of Medicine (CAM) is believed to be common [4]. However, data on its prevalence is not known.…”
Section: Discussionmentioning
confidence: 99%